Rural nurse administrators: Essentials for practice - Carol R. Eldridge; Sharon Judkins (Rural Nurse Organization; Binghamton University, 2012)
The rural practice setting has unique nursing and health care needs that significantly impact the role of rural nurse executives. This article describes aspects of the rural environment pertinent to rural nursing and helps identify the special competencies needed by nurses who work as managers and executives in rural settings.